Role of Hydrodistention and Intravesical Hyaluronic Acid in Treatment of Bladder Pain Syndrome: Case Report - Fanny Riana Ridwan; Bagus Baskoro Yusuf; Harrina Erlianti Rahardjo (Faculty of Medicine Universitas Indonesia, 2023)
Bladder pain syndrome (BPS) causes decreased mental and physical quality of life. The diagnosis and treatment of BPS must be made effective; however, the treatment of BPS was still not satisfactory for most patients. Two cases of BPS were presented to the urology clinic and were treated with a combination of hydrodistention and intravesical hyaluronic acid (HA) periodically. After 3-8 hydrodistension and hyaluronic acid instillation, the patients showed symptom improvement indicated by O’Leary Sant Questionnaire (symptom score 19-21 before treatment became 3-4 after treatment, problem score 8-16 before treatment became 0-2 after treatment), visual analogue scale (7-10 before treatment to 3-4 after treatment), and the global response assessment (GRA) scale were markedly improved. Both patients had glomerulations during cystoscopy, and the second had Hunner Lesion. A pathological examination of bladder biopsy specimens indicated acute and chronic inflammatory cell infiltration. The combination of hydrodistention and intravesical HA was beneficial for treating BPS in this study. Further study such as a clinical trial is needed to prove the efficacy and safety of this treatment.